ACTUATOR AND METHOD FOR MANUFACTURING ACTUATOR

By spirally wrapping the composite long body containing thermoplastic resin and conductive cable on the fiber polymer material, and fixing it by heating, the problem that the conductive cable cannot be fully fixed is solved, and efficient operation performance is achieved.

JP7665371B2Active Publication Date: 2025-04-21LINTEC CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021050121
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-24
Publication Date
2025-04-21
Estimated Expiration
2041-03-24

AI Technical Summary

Technical Problem

When the conductive cable is spirally wrapped around the fiber polymer material, the conductive cable may not be sufficiently secured, resulting in poor performance of the required action.

Method used

The composite elongate body containing thermoplastic resin and conductive cable is spirally wrapped around the fiber polymer material, and the composite elongate body is fused and fixed by heating.

Benefits of technology

Effectively fixing the conductive cable on the fiber polymer material improves the operational performance and makes it stable and in line with the expected operating performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007665371000002
    Figure 0007665371000002
  • Figure 0007665371000003
    Figure 0007665371000003
  • Figure 0007665371000001
    Figure 0007665371000001
Patent Text Reader

Abstract

To provide an actuator including a fibrous polymer material and a conductive yarn and having high effect of fixation of the conductive yarn to the fibrous polymer material, and a manufacturing method of the actuator.SOLUTION: An actuator has a fibrous polymer material (10) and a conjugated long body (20) containing a thermoplastic resin and a conductive yarn. The conjugated long body (20) is spirally wound around the fibrous polymer material (10). When total volume of the thermoplastic resin contained in the conjugated long body per meter is V1 and total surface area of the conductive yarn contained in the conjugated long body (20) per meter is A1, the actuator satisfies the following formula 1. 5[μm3 / μm2]≤V1 / A1≤60[μm3 / μm2] formula 1SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an actuator and a method for manufacturing the actuator. [Background technology]

[0002] Due to the advent of aging societies in developed countries, advances in robotics, and the shift towards intellectual activities among humans, there is a demand for powering a variety of items, and various actuators have been proposed. For example, Patent Document 1 discloses an actuator including a polymer fiber into which twist has been introduced in a coiled or non-coiled form.

[0003] An actuator including a polymer fiber having twist introduced into a non-coiled shape is formed by selecting a single filament or multifilament precursor polymer fiber (hereinafter also referred to as a fibrous polymer material) that is high strength and highly chain-oriented, and introducing twist into the fibrous polymer material to a level that does not produce coiling.

[0004] Actuators including coiled twisted polymer fibers are formed by introducing twist into the fibrous polymeric material either to the point where coiling occurs or to a level that does not produce coiling, and then introducing coiling in the same or opposite direction to the initially introduced twist.

[0005] Patent Document 1 discloses a non-electrochemical actuator that enables electrothermal operation by helically winding an electronic conductor (hereinafter also referred to as conductive yarn) such as a multi-walled carbon nanotube (MWNT) around a twist-spun nanofiber yarn segment, which is the fibrous polymer material. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2016-42783 A Summary of the Invention [Problem to be solved by the invention]

[0007] When a conductive thread is wound spirally around a fibrous polymer material, the conductive thread may not be sufficiently fixed to the fibrous polymer material and may come off, preventing the desired actuator performance from being obtained.

[0008] The present invention has been made in consideration of the above-mentioned circumstances, and aims to provide an actuator comprising a fibrous polymer material and a conductive thread, and which is highly effective in fixing the conductive thread to the fibrous polymer material, and a method for manufacturing the actuator. [Means for solving the problem]

[0009] The present invention has the following aspects. [1] A fibrous polymer material; A composite elongated body including a thermoplastic resin and a conductive thread, the composite long body is wound in a spiral shape around the fibrous polymer material, An actuator which satisfies the following formula 1, where V1 is the total volume of the thermoplastic resin contained per 1 m of the composite long body, and A1 is the total surface area of ​​the conductive yarn contained per 1 m of the composite long body. 5 [μm 3 / μm 2 ]≦V1 / A1≦60[μm 3 / μm 2 ] Formula 1 [2] A process of spirally winding a composite yarn obtained by combining a fusion yarn containing a thermoplastic resin and a conductive yarn around a fibrous polymer material; heating the composite yarn to fuse it to a surface of the fibrous polymeric material; A method for manufacturing an actuator comprising: A method for manufacturing an actuator, which satisfies the following formula 2 when the total volume of the fused yarns contained per 1 m of the composite yarn is V2 and the total surface area of ​​the conductive yarns contained per 1 m of the composite yarn is A2. 5 [μm 3 / μm 2 ]≦V2 / A2≦60[μm 3 / μm 2 ] Formula 2 [3] The method for manufacturing an actuator described in [2], wherein the composite yarn is a composite yarn obtained by combining the fusion yarn and the conductive yarn through twisting. Effect of the Invention

[0010] The actuator of the present invention comprises a fibrous polymer material and a conductive thread, and can provide an actuator in which the conductive thread is effectively fixed to the fibrous polymer material, as well as a method for manufacturing the actuator. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a schematic diagram illustrating an actuator according to an embodiment of the present invention. [Diagram 2] 5 is a manufacturing flow diagram of an actuator according to an embodiment of the present invention. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment of the present invention will be described with reference to the drawings as appropriate. In addition, the figures used in the following explanation may show key parts enlarged for convenience in order to make the features of the present invention easier to understand, and the dimensional ratios of each component may not necessarily be the same as the actual ones.

[0013] <Actuator> FIG. 1 is a schematic diagram showing an actuator 1 according to a first embodiment of the present invention. The actuator 1 comprises a fibrous polymer material 10 that is deformed by heating, and a composite elongated body 20 including a thermoplastic resin and a conductive thread, the composite elongated body 20 being spirally wound around the fibrous polymer material 10. When the total volume of the thermoplastic resin contained per meter of the composite elongated body 20 is V1 and the total surface area of ​​the conductive threads contained per meter of the composite elongated body 20 is A1, the following formula 1 is satisfied. 5 [μm 3 / μm 2 ]≦V1 / A1≦60[μm 3 / μm 2 ] Formula 1

[0014] In the actuator 1 of this embodiment, the composite long body 20 containing the conductive thread contains a thermoplastic resin, so that the conductive thread is highly fixed to the fibrous polymer material 10, and the desired actuator operating performance can be stably obtained.

[0015] [Fibrous polymer materials] The fibrous polymer material for obtaining an actuator that is driven by heating may be twisted in a coiled shape so as to wind a spiral, or may be twisted in a non-coiled shape while maintaining a linear shape without winding a spiral. In addition, the fibrous polymer material may be twisted in a non-coiled shape and then formed into a coiled shape by a method other than the twist introduction. A coiled or non-coiled twisted fibrous polymer material can be obtained, for example, by the method described in JP 2016-42783 A.

[0016] As an example of a polymer that constitutes a fibrous polymer material, nylon 6,6 is taken as an example. When a nylon 6,6 monofilament with a diameter of 250 μm is twisted in an environment of 25° C. by applying an appropriate tensile stress so as not to cause coiling, it can be rotated up to about 850 to 1150 times per meter. If the nylon 6,6 monofilament is twisted beyond this number of rotations, it will cause coiling or break.

[0017] When a nylon 6,6 monofilament with a diameter of 500 μm is twisted in an environment of 25° C. by applying an appropriate tensile stress thereto without causing coiling, it can rotate up to about 400 to 600 times per meter.

[0018] In this way, a fiber made of a polymer with a glass transition temperature higher than 25° C. can be twisted to just before coiling by applying an appropriate tensile stress in a temperature environment below the glass transition temperature of the polymer (e.g., 25° C.). The appropriate tensile stress is 4.5×10 times the tensile modulus of the fiber. -3 As a guideline, the size of the surrounding area should be about 1×10 of the tensile modulus of the fiber. -3 ~1×10 -2 Just double it.

[0019] When manufacturing a fibrous polymer material for obtaining an actuator that is driven by heat, the temperature environment in the step of twisting the fibers may be an environment at a temperature higher than the glass transition temperature of the polymer, preferably an environment at a temperature 10°C or higher than the glass transition temperature of the polymer, more preferably an environment at a temperature 20°C or higher than the glass transition temperature of the polymer. An environment at a temperature 40°C or higher than the glass transition temperature of the polymer is particularly preferable. By setting the temperature environment in the step of twisting the fibers at a higher temperature, the torque required to twist the fibers can be reduced, and it is also useful in that thick fibers or rigid fibers that previously required a very large torque can be easily twisted.

[0020] In a fibrous polymer material that has been twisted in a temperature environment close to the glass transition temperature of the polymer, in order to suppress the return of the twist to its original state, it is preferable to carry out a residual stress relaxation treatment, such as storing the material in an environment at or above the glass transition temperature of the polymer for a certain period of time.

[0021] In the actuator of the present invention, the glass transition temperature (Tg) of the polymer constituting the fibrous polymer material may be higher than 25° C. or may be higher than 45° C. For example, types of polymers include nylons such as nylon 6 (Tg: 45° C.) and nylon 6,6 (Tg: 47° C.), acrylic resins such as polymethyl methacrylate (Tg: 100° C.), polyester resins such as polyethylene terephthalate (Tg: 80° C.), polyvinyl chloride (Tg: 82° C.), polycarbonate (Tg: 150° C.), etc. In addition, types of polymers having a glass transition temperature (Tg) lower than 25° C. include polyethylene (Tg: −120° C.), polypropylene (Tg: −20° C.), etc.

[0022] The polymer constituting the fibrous polymer material is preferably crystalline. The degree of crystallinity of the polymer in the fibrous polymer material is preferably 50% or more, and more preferably 55% to 90%. When the degree of crystallinity is within such a range, it becomes easy to obtain a material with high anisotropy of molecular orientation and excellent effect as an actuator.

[0023] In the actuator of the present invention, the fibrous polymer material may be a monofilament fiber or may be made of a multifilament fiber.

[0024] [Compound long body] The composite elongated body 20 includes a thermoplastic resin and a conductive thread.

[0025] Examples of thermoplastic resins include polyolefins such as polyethylene and polypropylene; polyamides such as nylon 6, nylon 6,6 and nylon 6,10; polyethylene terephthalate; polyesters; and fluoropolymers such as polyvinylidene fluoride, with polyamides being preferred. The thermoplastic resin may be used alone or in combination of two or more kinds.

[0026] The melting temperature of the thermoplastic resin is preferably 60 to 180°C, more preferably 70 to 170°C, and even more preferably 80 to 160°C. When the melting temperature is equal to or higher than the lower limit of the range, the thermoplastic resin does not melt due to the heat generated when driving the actuator, and the effect of fixing the conductive thread to the fibrous polymer material 10 is sustained, making it easier to stably obtain the desired actuator operation performance. When the melting temperature is equal to or lower than the upper limit of the range, the step of heating the composite thread in the actuator manufacturing method described below can be performed at a heating temperature that does not damage the fibrous polymer material 10.

[0027] Examples of the conductive thread include metal wires, carbon nanotube conductive threads, conductive threads with metal-plated cores, etc., and conductive threads with metal-plated cores are preferred from the viewpoint of flexibility and light weight. Examples of the metal wire include stainless steel wires such as SUS302 and SUS304, tungsten wires, silver wires, gold wires, and wires made of two or more of these metals (for example, a metal surface plated with another metal). In the conductive thread having a metal-plated core, any plating method known in the art can be used without restriction to plate the core with a metal.

[0028] Examples of the core material include those made of polymers exemplified as polymers constituting the fibrous polymer material, such as nylons (nylon 6, nylon 6,6, nylon 6,10, etc.), polyether ether ketone, and polyvinylidene fluoride. The polymers may be used alone or in combination of two or more.

[0029] The melting temperature of the core material is preferably 50° C. or more higher than the melting temperature of the thermoplastic resin, more preferably 60° C. or more higher, and even more preferably 70° C. or more higher.

[0030] The metal to be plated is not particularly limited as long as the effects of the present invention can be obtained, but examples include gold, silver, copper, nickel, etc., with silver being preferred. The above metals may be used alone or in combination of two or more.

[0031] The diameter of the conductive thread is preferably 1 to 1000 μm, more preferably 5 to 500 μm, and even more preferably 10 to 100 μm. When the diameter of the conductive thread is equal to or greater than the lower limit of the above range, the conductivity is ensured and disconnection due to wear or the like can be suppressed. When the diameter of the conductive thread is equal to or less than the upper limit of the above range, flexibility and handleability are improved. In addition, inhibition of actuator movement is suppressed. In the above description, the conductive thread is assumed to be substantially circular, but it may be substantially elliptical. In this case, the diameter of the conductive thread is determined to be the average of the major axis and the minor axis of the substantially elliptical shape.

[0032] The number of conductive threads contained in the composite elongated body 20 is preferably 1 to 10, more preferably 1 to 7, and even more preferably 1 to 5. When the number of conductive threads is equal to or greater than the lower limit of the above range, the decrease in the conductivity of the actuator is suppressed. When the number of conductive threads is equal to or less than the upper limit of the above range, the fixing effect of the conductive threads to the fibrous polymer material is enhanced. In addition, the rigidity falls within an appropriate range. In addition, the proportion of thermoplastic resin contained in the composite elongated body 20 is not too small, improving adhesion. It is preferable that a portion of the conductive thread is exposed on the surface of the composite elongated body 20. By having a portion of the conductive thread exposed on the surface of the composite elongated body 20, poor contact is less likely to occur when the conductive thread is connected to an external power source.

[0033] When the total volume of the thermoplastic resin contained per meter of the composite long body 20 is V1 and the total surface area of ​​the conductive yarn contained per meter of the composite long body is A1, the following formula 1 is satisfied. 5 [μm 3 / μm 2 ]≦V1 / A1≦60[μm 3 / μm 2 ] Formula 1

[0034] V1 / A1 is 5 to 60 μm 3 / μm2 7 to 55 μm 3 / μm 2 It is preferable that the thickness is 10 to 30 μm. 3 / μm 2 When V1 / A1 is equal to or greater than the lower limit of the above range, the effect of fixing the conductive yarn to the fibrous polymeric material is enhanced. When V1 / A1 is equal to or less than the upper limit of the above range, the conductivity of the conductive yarn in the actuator is enhanced.

[0035] [Method of measuring V1 / A1] When the composite elongated body 20 is pulled while the actuator 1 is heated with a hair dryer or heat gun, the composite elongated body 20 can be peeled off from the fibrous polymer material 10. The mass per unit length (l1 [m]) of the obtained composite elongated body 20 is measured. The conductive thread is isolated from the composite elongated body 20, and the mass of the conductive thread contained per unit length (l1 [m]) of the composite elongated body 20 is measured. The difference between the mass per unit length (l1 [m]) of the composite elongated body 20 and the mass of the conductive thread contained per unit length (l1 [m]) of the composite elongated body 20 is calculated, and the mass of the thermoplastic resin contained per unit length (l1 [m]) of the composite elongated body 20 is calculated. From the obtained mass and the density of the thermoplastic resin, the volume (V1' [μm 3 The total volume V1 of the thermoplastic resin contained per meter of the composite elongated body 20 can be calculated from V1'×1 / l1. The diameter r2 [μm] of the conductive thread contained per unit length (l1 [m]) of the composite long body 20 isolated by the above method is measured by optical observation. The surface area of ​​the conductive thread contained per 1 m of the composite long body 20 is r2 × π × 1 × 10 6 [μm 2 When multiple conductive threads are included in the composite long body, calculate the surface area of ​​all the conductive threads and sum the total value to A2 (μm 2 The number of conductive threads can be confirmed by optical observation. In the above description, the conductive thread is assumed to be approximately circular, but it may be approximately elliptical. In that case, the average of the major and minor axes of the approximately ellipse should be taken as the diameter r2 [μm] of the conductive thread.

[0036] Furthermore, when the actuator 1 is manufactured by the actuator manufacturing method described below, V2 / A2 obtained by the method described below as a method for measuring V2 / A2 can be used as V1 / A1.

[0037] As shown in FIG. 1, the actuator 1 has a diameter D 10 The fibrous polymer material 10 has a diameter D 20 The composite long body 20 is spirally arranged with a predetermined gap interval I 20 It is wrapped around the wire.

[0038] As shown in FIG. 1, when the angle between the composite long body 20 and the fibrous polymer material 10 is θ, the pitch of the composite long body 20 is [I 20 +(D 20 / sinθ). The cross section of the fibrous polymer material 10 is 20 +(D 20 From the viewpoint of reducing the variation in the axial length (θ) of the ellipse, it is preferable that the ellipse is approximately circular. Although the description is based on the assumption that the ellipse is approximately circular, the ellipse may be approximately elliptical. In that case, the average of the major axis and the minor axis of the ellipse is the diameter D 10 This can be understood by replacing it with:

[0039] Diameter D of the fibrous polymer material 10 10 is 0.01 mm <D 10 ≦40mm, 0.05mm <D 10 ≦10mm, 0.1mm <D 10 ≦1mm. D 10 When the value is equal to or greater than the lower limit of the above range, mechanical damage such as breakage is unlikely to occur during or after processing or during operation, and the quality of the actuator is maintained. 10When is equal to or less than the upper limit of the above range, the movement that can be obtained from the unit length of the actuator can be made sufficiently large. In this specification, D 10 is the diameter D of the approximately cylindrical fibrous polymer material 10 in the actuator 10 can be measured at 5 to 10 randomly selected points and the average of these can be calculated.

[0040] Diameter D of composite long body 20 20 is 0.04 mm <D 20 ≦1.6mm, 0.1mm <D 20 ≦1.5mm, ≦0.2mm <D 20 It may be ≦1.4 mm. 20 When is equal to or greater than the lower limit of the range, the possibility of handling errors such as breakage of the composite elongated body 20 during the manufacture of the actuator 1 is reduced. 20 When is equal to or less than the upper limit of the above range, the risk of impeding the driving of the actuator 1 is reduced. The cross section of the composite elongated body 20 is described below on the assumption that it is substantially circular, but it may be substantially elliptical or flat. The major axis of the elliptical or flat shape is defined as a diameter D. 20 This can be understood by replacing it with: In this specification, D 20 is the length in the width direction of the composite elongated body 20 in a plan view when the actuator 1 is observed with an optical microscope (D in FIG. 1 20 ) can be measured at 5 to 10 randomly selected points and the average of these can be taken.

[0041] Diameter D of the fibrous polymer material 10 10 and the diameter D of the composite elongated body 20 20 The relationship is 0.1≦D 20 / D 10 <1.0 is preferable, and 0.2≦D 20 / D 10 ≦0.8 is more preferable, and 0.4≦D 20 / D 10 It is particularly preferred that D is ≦0.7. 20 / D10 When the thickness is within the above range, the driving of the actuator is not hindered and the conductive thread can be fixed to the fibrous polymer material.

[0042] Pitch of composite long body 20 [I 20 +(D 20 / sinθ)] is 0.01 mm ≤ [I 20 +(D 20 / sinθ)]≦5.0 mm, and 0.05 mm≦[I 20 +(D 20 / sinθ)]≦1.0 mm, and more preferably 0.1 mm≦[I 20 +(D 20 It is more preferable that [I / sinθ)]≦0.5 mm. 20 +(D 20 When the ratio (x, y) of the linear actuator (x, y) to the linear actuator (x, y) is within the above range, the actuator can be driven without being hindered and heat can be transmitted uniformly.

[0043] Diameter D of composite long body 20 20 and the gap interval I of the composite elongated body 20 20 0.5≦I 20 / D 20 ≦20, and 1≦I 20 / D 20 ≦10 is more preferable, and 2≦I 20 / D 20 It is particularly preferred that the ratio is ≦5. 20 / D 20 When the thickness is within the above range, the driving of the actuator is not hindered and the conductive thread can be fixed to the fibrous polymer material. In this specification, I 20 is the gap interval of the composite elongated body 20 in a plan view when the actuator 1 is observed with an optical microscope (I in FIG. 1 20 ) can be measured at 5 to 10 randomly selected points and the average of these can be taken.

[0044] The angle θ between the composite elongated body 20 and the fibrous polymer material 10 is 0°<θ<90°, preferably 20°≦θ≦70°, and more preferably 30°≦θ≦60°. When θ is within the above range, heat can be transferred uniformly over the entire length of the actuator without uneven heating. In this specification, θ can be the average of the angle (θ in Figure 1) formed between the composite elongated body 20 and the fibrous polymer material 10 when the actuator 1 is observed in a planar view with an optical microscope, measured at 5 to 10 randomly selected points.

[0045] In the actuator 1, the coverage of the composite elongated body 20 with respect to the outer surface area of ​​the actuator 1 in a plan view when observed with an optical microscope is preferably 10 to 60%, more preferably 20 to 50%, and even more preferably 30 to 40%. When the coverage is equal to or greater than the lower limit of the above range, the effect of fixing the conductive thread to the fibrous polymer material 10 is enhanced, and the effect of preventing the conductive thread from falling off is enhanced. As a result, it becomes easier to stably obtain the desired actuator operation performance. When the coverage is equal to or less than the upper limit of the above range, the adverse effect of the coverage on the actuator operation can be reduced. In addition, the amount of thermoplastic resin used can be reduced, which is economical. In this specification, the coverage can be determined by the following method. When the actuator 1 is observed under an optical microscope in a plan view, the length (L1i) occupied by the composite elongated body 20 and the length (L2i) of the portion not covered by the composite elongated body 20 in any straight line in the axial direction of the actuator 1 (axial direction of the fibrous polymer material 10) are measured (FIG. 1). The sum of the measured L1i is defined as L1, the sum of the measured L2i is defined as L2, and the coverage rate can be calculated as L1 / (L1+L2)×100.

[0046] A method for fixing a conductive thread to a fibrous polymer material has been known to use a liquid adhesive containing an organic solvent. Specifically, a liquid adhesive is applied to a fibrous polymer material around which a conductive thread is wound in a spiral shape, and then the adhesive is dried to form an adhesive layer. However, when a liquid adhesive containing an organic solvent is used, an additional step of drying the organic solvent is required, which complicates the manufacturing process of the actuator. In addition, since the liquid adhesive is applied to the entire surface of the fibrous polymer material around which the conductive thread is wound in a spiral shape, the conductive thread is completely covered by the adhesive layer, making it difficult to connect external power. Forming an adhesive layer so as not to cover a portion of the conductive yarn makes the process more complicated and makes quality control difficult. On the other hand, in the manufacturing method of the actuator of this embodiment, as described below, the composite yarn containing the conductive yarn is wound around a fibrous polymer material and then heated, so that it is not necessary to use an organic solvent, the manufacturing process is simple, and it is advantageous in that the above-mentioned coverage rate can be easily controlled to a constant level.

[0047] <Actuator manufacturing method> The method for manufacturing the actuator of this embodiment includes a step of spirally winding a composite yarn 20', which is a composite of a fusion yarn containing a thermoplastic resin and a conductive yarn, around a fibrous polymer material 10 (hereinafter also referred to as "step 1"), and a step of heating the composite yarn to fuse it to the surface of the fibrous polymer material (hereinafter also referred to as "step 2") (Fig. 2). When the total volume of the fusion yarns contained per 1 m of the composite yarn is V2 and the total surface area of ​​the conductive yarns contained per 1 m of the composite yarn is A2, the following formula 2 is satisfied. 5 [μm 3 / μm 2 ]≦V2 / A2≦60[μm 3 / μm 2 ] Formula 2

[0048] According to the method for producing the actuator of this embodiment, the fusion yarn contained in the composite yarn 20' is melted, so that the composite yarn 20' becomes a composite long body 20, and the above-mentioned actuator 1 can be produced. Each step will be described below.

[0049] [Process 1] The fibrous polymer material 10 used in step 1 can be the same as the fibrous polymer material described in the actuator 1 above. In step 1, a composite yarn 20', which is a composite of a fusible yarn containing a thermoplastic resin and a conductive yarn, is wound spirally around the fibrous polymer material 10. The winding density, which is expressed as the number of winds of the composite yarn per meter of the fibrous polymer material, is determined by the pitch [I 20 +(D 20 / sinθ), the angle θ between the composite long body 20 and the fibrous polymeric material 10, etc. may be within a predetermined range, and is preferably 500 to 10,000 turns / m, more preferably 1,000 to 8,000 turns / m, and even more preferably 2,000 to 6,000 turns / m. The predetermined angle θ is the preferred range of θ explained for the actuator 1 above.

[0050] The composite yarn 20' used in step 1 is a composite yarn obtained by combining a fusion yarn containing a thermoplastic resin and a conductive yarn. The conductive yarn used in the composite yarn can be the same as the conductive yarn described in the actuator 1 above. The fusion yarn used in the composite yarn can be, for example, a filament of the thermoplastic resin described in the actuator 1 above. The diameter of the fusion yarn may be 0.05 to 0.6 mm, 0.1 to 0.5 mm, or 0.2 to 0.4 mm. When the diameter of the fusion yarn is equal to or greater than the lower limit of the range, the effect of fixing the conductive yarn to the fibrous polymer material is enhanced. When the diameter of the fusion yarn is equal to or less than the upper limit of the range, the decrease in the conductivity of the actuator is suppressed.

[0051] The method of compounding is not particularly limited as long as the effects of the present invention can be obtained, but twisting is preferred. When the composite yarn is composited by twisting yarn, the number of twists per meter is preferably 100 to 10,000 T / m, more preferably 500 to 5,000 T / m, and even more preferably 1,000 to 3,000 T / m. When the number of twists per meter is within the above range, unraveling of the twisted yarn is suppressed in the step of spirally winding the composite yarn around the fibrous polymer material, and after the fusion step, the fixing effect of the conductive yarn to the fibrous polymer material is enhanced, and heat transfer of the actuator is improved.

[0052] The number of fusion yarns contained in the composite yarn is preferably 1 to 10, more preferably 1 to 7, and even more preferably 1 to 5. When the number of fusion yarns is equal to or greater than the lower limit of the above range, the effect of fixing the conductive yarn to the fibrous polymer material is enhanced. When the number of fusion yarns is equal to or less than the upper limit of the above range, the decrease in the conductivity of the actuator is suppressed.

[0053] The number of conductive yarns contained in the composite yarn is preferably 1 to 10, more preferably 1 to 7, and even more preferably 1 to 5.

[0054] The ratio of the number of fusible yarns to the number of conductive yarns contained in the composite yarn, that is, the number of fusible yarns:the number of conductive yarns, is preferably 1:2 to 4:1, and more preferably 1:1 to 2:1.

[0055] [Process 2] In step 2, the composite yarn is heated to fuse to the surface of the fibrous polymer material 10. The heating temperature is not particularly limited as long as it is a temperature at which the thermoplastic resin contained in the fusion yarn can be melted, and may be, for example, the melting temperature of the thermoplastic resin to melting temperature + 60°C, preferably melting temperature + 10°C to melting temperature + 50°C, and more preferably melting temperature + 20°C to melting temperature + 40°C. When the heating temperature is equal to or higher than the lower limit of the above range, the thermoplastic resin melts and bonds the fibrous polymer material 10 to the conductive thread, improving the effect of fixing the conductive thread to the fibrous polymer material, making it easier to stably obtain the desired actuator operation performance. When the heating temperature is equal to or lower than the upper limit of the above range, the fibrous polymer material is less likely to be damaged.

[0056] When the total volume of the fusion yarn contained per meter of the composite yarn is V2 and the total surface area of ​​the conductive yarn contained per meter of the composite yarn is A2, the following formula 2 is satisfied. 5 [μm 3 / μm 2 ]≦V2 / A2≦60[μm 3 / μm 2 ] Formula 2

[0057] V2 / A2 is 5 to 60 μm 3 / μm 2 7 to 55 μm 3 / μm 2 It is preferable that the thickness is 10 to 30 μm. 3 / μm 2 When V2 / A2 is equal to or greater than the lower limit of the above range, the effect of fixing the conductive yarn to the fibrous polymer material is enhanced. When V2 / A2 is equal to or less than the upper limit of the above range, the decrease in the conductivity of the actuator is suppressed. In addition, since the total volume of the fused yarns and the total surface area of ​​the conductive yarns do not substantially change before and after fusion, V2 / A2 will be the same value as V1 / A1 in the manufactured actuator.

[0058] [Method of measuring V2 / A2] The diameter of the fusion yarn is r 1’ [μm], the volume per 1 m of fusion yarn is (r 1’ / 2) 2 ×π×1×10 6 [μm 3 When multiple fusion yarns are used, calculate the volume of each fusion yarn and sum it up to V2 [μm 3 ] can be used. The diameter of the conductive thread is r 2’[μm], the surface area of ​​the conductive yarn is r 2’ ×π×1×10 6 [μm 2 When multiple conductive threads are used, calculate the surface area of ​​each conductive thread and sum it up to A2 [μm 2 ] can be used. In the above description, the fusion yarn and the conductive yarn are assumed to be substantially circular, but they may be substantially elliptical. In that case, the average of the major axis and the minor axis of the substantially elliptical shape is the diameter r of the fusion yarn. 1’ [μm] and diameter r of conductive thread 2’ It is best to enter it in [μm].

[0059] Although the embodiments of the present invention have been described in detail above with reference to the drawings, each configuration and their combination in the embodiments is merely an example, and addition, omission, substitution, and other modifications of the configuration are possible without departing from the spirit of the present invention. Furthermore, the present invention is not limited to each embodiment, but is limited only by the scope of the claims. EXAMPLES

[0060] The present invention will be described in more detail below with reference to specific examples, although the present invention is not limited to the following examples.

[0061] [V1 / A1 measurement] The diameter of the fusion yarn is r 1’ [μm], and the volume per 1 m of fusion yarn is (r1 / 2) 2 ×π×1×10 6 [μm 3 When multiple fusion yarns are used, the volume of each fusion yarn is calculated, and the sum is calculated as V2 (V1) [μm 3 ]. The diameter of the conductive thread is r 2’ [μm], the surface area of ​​the conductive yarn is r 2’ ×π×1×10 6 [μm 2 When multiple conductive threads are used, the surface area of ​​each of the conductive threads is calculated and the sum is calculated as A2 (A1) [μm2 ].

[0062] [Evaluation of adhesiveness of conductive thread] The actuators created using the method described below were cut short-side down into 10 pieces measuring 1 cm each, and the ends were observed under a microscope. Those that did not find any gaps between the fibrous polymer material and the composite long body were judged to have good adhesion, and those that found gaps were judged to have poor adhesion. The 10 pieces x both ends were used as the measurement points, for a total of 20 points, and the percentage of those with good adhesion was calculated and judged as follows: ·judgement Good adhesion rate exceeds 85%...A Good adhesion rate: over 50% and under 85% B The percentage of good adhesion is 50% or less...C

[0063] [Continuity evaluation] The electrical resistance was measured using the four-terminal method under the following conditions over the entire length of the actuator (1m) created using the method described below, and the connection of the conductive thread to the outside was evaluated. A resistance of less than 10kΩ was considered good, and a resistance of 10kΩ or more was considered poor. The percentage of good points out of all measurement points was calculated and judged as follows: ·conditions Actuator feed speed: 10mm / s Measurement interval: 0.2s Terminal distance: 40mm Terminal diameter: 10mm Measurement points: Approximately 500 points ·judgement The percentage of good conductivity is over 98%...A The percentage of good conductivity is over 70% and 98% or less...B The percentage of good conductivity is 70% or less...C

[0064] [comprehensive evaluation] In the above evaluation results, when both the adhesion evaluation and the conductivity evaluation were "A", the overall evaluation was judged to be "A". When the adhesion evaluation and the conductivity evaluation were "A" or "B" and there was one or less "A", the overall evaluation was judged to be "B". When either or both of the adhesion evaluation and the conductivity evaluation were "C", the overall evaluation was judged to be "C". Additionally, overall ratings of A and B were considered passes, and C was considered a fail.

[0065] [Raw materials used] Nylon filament (Toray Monofilament Co., Ltd., nylon 66, diameter: 0.5 mm) Copolymer nylon fusion thread (manufactured by Unitika Ltd., product name: Flor M, diameter: 100 denier, melting temperature: 130°C) Conductive thread (Osaka Electric Industry Co., Ltd., product name: ODEX30d, silver-plated core thread, diameter: 30 denier)

[0066] [Example 1] Nylon filaments were twisted at 600 T / m and heat-treated at 180°C for 40 minutes to obtain a fibrous polymer material. One conductive yarn and one fusion yarn were twisted at 1000 T / m to obtain a composite yarn. The composite yarn was spirally wound around the fibrous polymer material at 1000 T / m and heat-treated at 130°C for 5 minutes to adhere the composite yarn to obtain actuator 1. V1 / A1 of actuator 1 was 14 μm. 3 / μm 2 The results of the adhesiveness and conductivity evaluation of the conductive yarn are shown in Table 1.

[0067] [Example 2] Actuator 2 was obtained in the same manner as in Example 1, except that the composite yarn was made of two conductive yarns and one fusion yarn. The V1 / A1 of actuator 2 was 7 μm. 3 / μm 2 The results of the adhesiveness and conductivity evaluation of the conductive yarn are shown in Table 1.

[0068] [Example 3] Actuator 3 was obtained in the same manner as in Example 1, except that one conductive yarn and two fusible yarns were used in preparing the composite yarn. V1 / A1 of actuator 3 was 27 μm. 3 / μm 2 The results of the adhesiveness and conductivity evaluation of the conductive yarn are shown in Table 1.

[0069] [Example 4] Actuator 4 was obtained in the same manner as in Example 1, except that one conductive yarn and four fusion yarns were used in preparing the composite yarn. V1 / A1 of actuator 4 was 55 μm. 3 / μm 2 The results of the adhesiveness and conductivity evaluation of the conductive yarn are shown in Table 1.

[0070] [Comparative Example 1] Except for using one conductive yarn instead of the composite yarn, an actuator 5 was obtained in the same manner as in Example 1. Since no fusible yarn was included, V1 / A1 of the actuator 5 was 0 μm. 3 / μm 2 The results of the adhesiveness and conductivity evaluation of the conductive yarn are shown in Table 1.

[0071] [Comparative Example 2] Actuator 6 was obtained in the same manner as in Example 1, except that four conductive yarns and one fusion yarn were used to prepare the composite yarn. V1 / A1 of actuator 6 was 3 μm. 3 / μm 2 The results of the adhesiveness and conductivity evaluation of the conductive yarn are shown in Table 1.

[0072] [Comparative Example 3] Actuator 7 was obtained in the same manner as in Example 1, except that one conductive yarn and eight fusion yarns were used in preparing the composite yarn. V1 / A1 of actuator 7 was 110 μm. 3 / μm 2 The results of the adhesiveness and conductivity evaluation of the conductive yarn are shown in Table 1.

[0073] [Table 1]

[0074] The actuators of Examples 1 to 4 were evaluated as being good in terms of adhesiveness and conductivity. 3 / μm 2 In Comparative Example 2, where V1 / A1 is 110 μm, the adhesiveness is poor. 3 / μm 2 In Comparative Example 3, the electrical conductivity was poor. [Industrial Applicability]

[0075] The actuator of the present invention can be used as an actuator that deforms when heated in applications for motorizing a variety of items. [Explanation of symbols]

[0076] 1 Actuator, 10 Fibrous polymer material, 20 Composite long body, 20' Composite yarn, I 20 ... the gap between adjacent composite long bodies of the spiral structure of the composite long body, D 10 ...Diameter of fibrous polymer material, D 20 θ: the angle between the composite long body and the fibrous polymer material; L1i: the length of the composite long body; L2i: the length of the part of the composite long body that is not covered

Claims

1. A fibrous polymer material; Conductive yarn and thermoplastic resin (however, in the case where the fibrous polymer material contains a thermoplastic resin, the thermoplastic resin contained in the fibrous polymer material is excluded. In the case where the conductive thread contains a thermoplastic resin, the thermoplastic resin contained in the conductive thread is excluded. The polymer constituting the fibrous polymer material is nylon 6, nylon 6,6, polymethyl methacrylate, polyethylene terephthalate, polyvinyl chloride, or polycarbonate; The thermoplastic resin has a melting temperature of 60 to 180° C. the composite long body is wound in a spiral shape around the fibrous polymer material, An actuator which satisfies the following formula 1, where V1 is the total volume of the thermoplastic resin contained per 1 m of the composite long body, and A1 is the total surface area of ​​the conductive yarn contained per 1 m of the composite long body. 5 [μm 3 / μm 2 ≤ V1 / A1 ≤ 60 [μm 3 / μm 2 Equation 1

2. A step of spirally winding a composite yarn obtained by combining a fusion yarn containing a thermoplastic resin and a conductive yarn around a fibrous polymer material; heating the composite yarn to fuse it to a surface of the fibrous polymeric material; A method for manufacturing an actuator comprising: The polymer constituting the fibrous polymer material is nylon 6, nylon 6,6, polymethyl methacrylate, polyethylene terephthalate, polyvinyl chloride, or polycarbonate; The thermoplastic resin has a melting temperature of 60 to 180° C. A method for manufacturing an actuator, which satisfies the following formula 2 when the total volume of the fusion yarns contained per 1 m of the composite yarn is V2 and the total surface area of ​​the conductive yarns contained per 1 m of the composite yarn is A2. 5 [μm 3 / μm 2 ≤ V2 / A2 ≤ 60 [μm 3 / μm 2 Equation 2

3. The method for manufacturing an actuator according to claim 2 , wherein the composite yarn is a composite yarn obtained by combining the fusion yarn and the conductive yarn through twisting.

Citation Information

Patent Citations

  • Electroconductive composite yarn and electroconductive fabric

    JP2008013874A

  • Coiled and non-coiled twisted nanofiber yarn and polymer fiber torsional and tensile actuators

    JP2016042783A

  • Actuator

    JP2019026966A

  • Actuator and method for manufacturing actuator

    JP2021065075A

  • Conductors embedded in polymer artificial muscle actuators

    JP2021503352A